Mle046 Is a Marine Mesophilic MHETase-Like Enzyme - Meyer-Cifuentes, Ingrid E.; Öztürk, Başak (Frontiers in Microbiology, 2021)
Accumulation of plastics in the oceans presents a major threat to diverse ecosystems. The introduction of biodegradable plastics into the market aims to alleviate the ecological burden caused by recalcitrant plastics. Poly (butylene adipate-co-terephthalate) (PBAT) is a biodegradable commercial plastic that can be biodegraded similarly to polyethylene terephthalate (PET) by PETase-like enzymes and MHETases. The role of MHETases is to hydrolase the intermediate degradation product of PET, mono-2-hydroxyethyl terephthalate (MHET) to its monomers. We recently identified a homolog of the MHETase of the PET-degrading bacterium Ideonella sakaiensis, Mle046, from a marine microbial consortium. In this consortium, Mle046 was highly expressed when a PBAT-based blend film (PF) was supplied as the sole carbon source. In this study, we recombinantly expressed and biochemically characterized Mle046 under different conditions. Mle046 degrades MHET but also 4-(4-hydroxybutoxycarbonyl) benzoic acid (Bte), the intermediate of PF degradation. Mle046 is a mesophilic enzyme adapted to marine conditions, which rapidly degrades MHET to terephthalate and ethylene glycol at temperatures between 20 °C and 40 °C. Mle046 degradation rates were similar for Bte and MHET. Despite its mesophilic tendency, Mle046 retains a considerable amount of activity at temperatures ranging from 10 °C to 60 °C. In addition, Mle046 is active at a range of pH values from 6.5 to 9. These characteristics make Mle046 a promising candidate for biotechnological applications related to plastic recycling.